Analyses of Maximum Precipitation in Brazil and the Variability of Diurnal Cycle - Aléxia Monteiro Valentim; Cláudio Moisés Santos e Silva; Daniele Tôrres Rodrigues; Paula Andressa Alves de Araújo (Environmental Sciences Proceedings, 2023)
According to recent works, the diurnal cycle is more geographically pronounced in places such as South America; and this analysis aims to observe how climate variability is associated with meteorological phenomena at different scales. For this, a set of hourly data from rain gauges throughout Brazil was collected, and through 411 automatic rain gauges, the data were selected between 1 January 2008 and 31 December 2020. Clustered multivariate statistics were performed for regional characterization of the data, with sets of 4, 5, and 6 groups. The identification of the occurrence of different daily cycles on the sub-daily scale demonstrates intense rainfall associated with different meteorological phenomena and spatial variations.